Level of adherence to the treatment of patients with gestational diabetes mellitus in the high-risk pregnancy outpatient in the city of Cascavel/PR (Research, Society and Development, 2023)
Pregnancy is a physiological phenomenon that encompasses numerous changes, the main ones involving the woman's metabolism. In view of this, it is known that some alterations result in an irregular gestational course, resulting in greater chances of complications, interference and death for the maternal-fetal binomial, thus determining the so-called high-risk pregnancy. Among the various etiopathogenesis there is gestational diabetes mellitus (GDM), which, through the effectiveness of its treatment, results in a reduction of possible unfavorable outcomes during and after pregnancy. Thus, this study aimed to carry out a quantitative survey through the application of questionnaires on the level of adherence to the treatment of women diagnosed with GDM, as well as the identification of the main factors that prevent adequate adherence in a pregnancy outpatient clinic in high risk in the city of Cascavel/PR. 42 women were interviewed, based on the application of a general questionnaire, the Morisky-Green test and adaptation of the self-care activities questionnaire. In general, adherence to and implementation of dietary and drug therapies and glycemic monitoring occurred effectively, expressing a statistically significant value (> 50%). On the other hand, physical activity was the pillar with the lowest adherence and daily performance. In addition, it was possible to conclude that financial condition and work are the main reasons for not following effective therapy among participants who indicated some causal factor.